AKURASI PEMASANGAN NASAL KANUL BERHUBUNGAN DENGAN PERUBAHAN SATURASI OKSIGEN PADA PASIEN DI ICU - Purnajaya, Heri; Maryana; Erwanto, Fredi (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Oxygen supply deficit will result in hypoxemia, brain damage, and can threaten a person's life. Data from Panembahan Senopati regional public hospital in Bantul showed that 433 (20.5%) patients with impaired oxygenation obtained oxygen therapy through nasal cannulae. Oxygen therapy with nasal cannulae which administered accurately is expected to maintain the oxygen demand in body tissues, so the oxygen saturation remains within a normal range. Objective: This research aimed to investigate the correlation between the accuracy of installing the oxygenation tools using nasal cannulae and the changes in the oxygen saturation in patients with impaired oxygenation. Methods: This research used a descriptive analytic method with a cross-sectional approach. The sampling technique used was total sampling with 34 samples. Data were collected with a checklist. The analysis technique used Spearman's Rho. Results: The accuracy of installing the oxygenation tool using nasal cannulae was mostly categorized as accurate (52%). The average change in oxygen saturation in patients with impaired oxygenation was 2.86%. The correlation between the accuracy of installing the oxygenation tool using nasal cannulae and changes in the oxygen saturation in patients with impaired oxygenation was significant (p=0.016). Conclusion: There was a significant correlation between the accuracy of installing oxygenation tool using nasal cannulae and the oxygen saturation changes in patients with impaired oxygenation. Keywords: Oxygen Therapy, Oxygen Saturation, Impaired Oxygenation.